Physical Transformation of Streetscape Post Urban Rejuvenation and Revitalization: Case of Banjarmasin’s “Kota Lama” - Chairil Zidane (Interdisciplinary Social Studies, 2025)
Streetscape plays a crucial role in shaping the visual identity of urban areas and supporting the function of public spaces as hubs for social interaction and creative economic activities. This study examines the physical transformation of streetscape elements in the “Old City” of Banjarmasin across three phases: pre-intervention (2015–2017), post-rejuvenation (2018–2020), and post-revitalization (2021–2023). Using Habraken’s theory of Form, the Physical Order with its levels of intervention—support, infill, and treatments—this research employs qualitative methods, including literature review and visual documentation through Google Maps and Google Street View. The analysis focuses on streetscape components such as roads, building elements, and street furniture. Findings reveal that before intervention, the streetscape appeared basic and lacked regional identity. The rejuvenation phase brought aesthetic improvements through paving blocks, guiding blocks, signage, and the addition of furniture. The revitalization phase introduced more profound changes, including adaptive reuse of old shophouses, murals, creative signage, and rearranged façades, which collectively strengthened the area’s visual identity. These transformations demonstrate a progression from support to infill and treatments, resulting in a dynamic, adaptive environment aligned with the socio-cultural needs of modern communities, particularly Generation Z. The study contributes theoretically to housing and settlement architecture and provides practical insights for sustainable urban rejuvenation and revitalization projects, highlighting the novelty of applying the levels of intervention framework to streetscape transformation.